Characterization of Magnaporthe oryzae Chrysovirus 1 Structural Proteins and Their Expression in Saccharomyces cerevisiae - Urayama, Syunichi (American Society for Microbiology, 2012)
Magnaporthe oryzae chrysovirus 1 (MoCV1), which is associated with an impaired growth phenotype of its host fungus, harbors four major proteins: P130 (130 kDa), P70 (70 kDa), P65 (65 kDa), and P58 (58 kDa). N-terminal sequence analysis of each protein revealed that P130 was encoded by double-stranded RNA1 (dsRNA1) (open reading frame 1 [ORF1] 1,127 amino acids [aa]), P70 by dsRNA4 (ORF4; 812 aa), and P58 by dsRNA3 (ORF3; 799 aa), although the molecular masses of P58 and P70 were significantly smaller than those deduced for ORF3 and ORF4, respectively. P65 was a degraded form of P70. Full-size proteins of ORF3 (84 kDa) and ORF4 (85 kDa) were produced in Escherichia coli. Antisera against these recombinant proteins detected full-size proteins encoded by ORF3 and ORF4 in mycelia cultured for 9, 15, and 28 days, and the antisera also detected smaller degraded proteins, namely, P58, P70, and P65, in mycelia cultured for 28 days. These full-size proteins and P58 and P70 were also components of viral particles, indicating that MoCV1 particles might have at least two forms during vegetative growth of the host fungus. Expression of the ORF4 protein in Saccharomyces cerevisiae resulted in cytological changes, with a large central vacuole associated with these growth defects. MoCV1 has five dsRNA segments, as do two Fusarium graminearum viruses (FgV-ch9 and FgV2), and forms a separate clade with FgV-ch9, FgV2, Aspergillus mycovirus 1816 (AsV1816), and Agaricus bisporus virus 1 (AbV1) in the Chrysoviridae family on the basis of their RdRp protein sequences.